Perioperative oxidative stress predicts subsequent pain-related outcomes in the 6 months after total knee arthroplasty. Issue 1 (4th January 2023) - Bruehl, Stephen; Milne, Ginger; Schildcrout, Jonathan; Shi, Yaping; Anderson, Sara; Shinar, Andrew; Polkowski, Gregory; Mishra, Puneet; Billings, Frederic T.
Abstract : Supplemental Digital Content is Available in the Text. Elevated perioperative oxidative stress prospectively predicts greater knee pain intensity 6 months after total knee arthroplasty in older adult patients with osteoarthritis. Abstract: Total knee arthroplasty (TKA) is effective for pain reduction in most patients, but 15% or more report unsatisfactory long-term pain outcomes. We tested whether oxidative stress (OS) related to extended tourniquet application during TKA and subsequent ischemic reperfusion (IR) contributed to adverse post-TKA pain outcomes. Blood samples were obtained in 91 patients with osteoarthritis (63% female) undergoing TKA before tourniquet placement (T1), 45 minutes after tourniquet inflation (T2), and 15 minutes after tourniquet removal (T3). Plasma levels of F2 -isoprostanes and isofurans, the most specific measures of in vivo OS, were quantified. Pain intensity and function were assessed at baseline and again at 6 weeks and 6 months after TKA. Results indicated that higher Combined OS (F2 -isoprostanes + isofurans/2) at T1 baseline and larger increases in Combined OS from T1 to T2 were associated with higher baseline-corrected past 24-hour worst and average pain intensity (numeric rating scale) and higher past week McGill Pain Questionnaire-2 total scores at 6-month follow-up ( P 's < 0.05). Increases in Combined OS from T1 to T3, which should most directly capture OS and IR injury related to tourniquet use, were not associated with short-term or long-term post-TKA pain outcomes. Longer ischemia duration was unexpectedly associated with lower baseline-corrected pain intensity at 6-month follow-up. Combined OS was not linked to functional outcomes at either follow-up. Elevated perioperative OS seems to exert small but significant adverse effects on long-term post-TKA pain outcomes, although this OS seems unrelated to IR injury associated with extended tourniquet use.